2019
DOI: 10.1111/iju.14103
|View full text |Cite
|
Sign up to set email alerts
|

Impact of post‐void residual urine volume on intravesical recurrence after nephroureterectomy for upper urinary tract urothelial carcinoma

Abstract: Abbreviations & Acronyms BPH = benign prostatic hyperplasia CI = confidence interval GC = gemcitabine, cisplatin HR = hazard ratio LUTS = lower urinary tract symptoms PSM = propensity scorematching RFS = recurrence-free survival TUR-P = transurethral resection of the prostate UC = urothelial carcinoma UUT-UC = upper urinary tract urothelial carcinoma Objective: To examine the impact of post-void residual urine volume on the risk of postoperative recurrence of intravesical carcinoma in patients with upper urina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…This result suggests that not only residual urine, but also pyuria and residual urine contribute to the recurrence of cancer. 4 The pathways of recurrence or multifocality of urothelial carcinoma have been considered. The monoclonality hypothesis and field cancerization hypothesis were reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This result suggests that not only residual urine, but also pyuria and residual urine contribute to the recurrence of cancer. 4 The pathways of recurrence or multifocality of urothelial carcinoma have been considered. The monoclonality hypothesis and field cancerization hypothesis were reported.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of a residual urine volume was defined as ≥30 mL according to our previous report. 4 The presence of pyuria was defined as ≥10 white blood cells per high-powered field at the time before TUR-Bt.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 The authors previously showed that the presence of residual urine and pyuria were risk factors for intravesical recurrence after nephroureterectomy for upper urinary tract carcinoma. 2 In this article, they showed that the presence of residual urine and pyuria were two independent prognostic factors for intravesical recurrence after transurethral resection of non-muscle invasive bladder cancer, as shown in upper urinary tract carcinoma. After patients were classified into risk groups, the poor-risk group (patients with both pyuria and residual urine) showed a significantly short recurrencefree survival compared with that of the good-(patients with neither of them) and intermediate-risk groups (patients with either one).…”
Section: Editorial Commentmentioning
confidence: 91%
“…Sazuka et al . investigated the association between post‐void residual urinary volume and IVR after RNU, and concluded that the presence of residual urine (defined as ≥30 mL) might be a hotbed of IVR . Although the definition of “presence” of a post‐void residual volume of 30 mL requires further investigation, their findings showed that non‐severe residual volumes are associated with a higher risk of IVR after RNU.…”
mentioning
confidence: 99%